SISTEM PENDUKUNG KEPUTUSAN PENILAIAN KINERJAKARYAWAN KONTRAK DENGAN MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING: (Studi Kasus: PT.Tirta Sukses Perkasa) - Mina Ismu Rahayu; Amelia Rahayu Dwi Putri (LPPM STMIK Bandung, 2021)
Subjective decision-making can lead to social disparities between employees so that it can hinder company performance. In contract extension, managers often experience difficulties in determining contract extensions because of the large number of candidates and also the many criteria used in the assessment. Therefore we need a decision support system that can support the decision making of employee extension so that managers can make decisions quickly, precisely and accurately. This decision support system uses the SAW (Simple Additive Weighting) method where this method can be used to overcome existing complexities, because of the many alternatives and criteria that must be considered in employee contract extensions such as discipline, attendance, work quality, and cooperation. The data used is an assessment of employee extension at PT.Tirta Sukses Perkasa System testing is carried out based on existing data at PT.Tirta Sukses Perkasa that is by comparing the results of Microsoft Excel calculations with the results of the system calculations that have been made.The results of the implementation of the decision support system for employee contract extension with the SAW (Simple Additive Weighting) method were made to assist in the decision-making process based on the optimal competency value of employees. So it can be used for employee contract extensions.